Analisis Kinerja Sistem Televisi Digital Didasarkan Pada Standar International Telecomunication Union - Jauhariyatul Fajriyah; Hudiono Hudiono; Nugroho Suharto (Jurnal Jaringan Telekomunikasi, 2021)
This study aims to determine the effect of the selection of the DVB-T2 parameter value on system performance. The parameters used are the parameters of Bandwidth, FFT size, Guard Interval, and Modulation Technique. The parameter values ??used are in accordance with those recommended by the ITU. System performance is observed by performing calculations and simulations. The simulation is carried out with the help of MATLAB software. The results of the simulation are observed with BER and SNR values ??to see the effect of fft size, Guard Interval and modulation techniques, while the effect of bandwidth values ??is observed by performing calculations. The results obtained show that the 10 MHz bandwidth has the largest channel capacity value with an increase of 25% from the 8MHz bandwidth value. Simulations carried out at the FFT size show that it does not have much effect on the performance of the DVB-T2 system. In the simulation, the Guard Interval value shows that the use of the Guard Interval value does not really affect the BER and SNR values, while the calculation of the effect of the Guard Interval on the maximum transmission distance in SFN mode shows that the maximum distance is generated with a Guard Interval value of 19/128 with an FFT value of 32K. with a distance of 159.5 Km. In the simulation of the modulation technique, the results show that QPSK has the best BER resistance compared to other modulation techniques, this is also in line with the results of the calculations.